Pattern Recognition in Histopathological Images: An ICPR 2010 Contest - Gurcan, Metin N.; Madabhushi, Anant; Rajpoot, Nasir (Recognizing Patterns in Signals, Speech, Images and Videos, 2010)
The advent of digital whole-slide scanners in recent years has spurred a revolution in imaging technology for histopathology. In order to encourage further interest in histopathological image analysis, we have organized a contest called “Pattern Recognition in Histopathological Image Analysis.” This contest aims to bring some of the pressing issues facing the advance of the rapidly emerging field of digital histology image analysis to the attention of the wider pattern recognition and medical image analysis communities. Two sample histopathological problems are explored: counting lymphocytes and centroblasts. The background to these problems and the evaluation methodology are discussed.